Eating disorders in adolescence: attachment issues from a developmental perspective - Gander, Manuela; Sevecke, Kathrin; Buchheim, Anna (Frontiers in Psychology, 2015)
In the present article we review findings from an emerging body of research on attachment issues in adolescents with eating disorders from a developmental perspective. First, we will outline the crucial developmental changes in the attachment system and discuss how they might be related to the early onset of the disease. Then we will report on the major results from attachment studies using self-report and narrative instruments in that age group. Studies with a developmental approach on attachment will be analyzed in more detail. The high incidence of the unresolved attachment pattern in eating disorder samples is striking, especially for patients with anorexia nervosa. Interestingly, this predominance of the unresolved category was also found in their mothers. To date, these transgenerational aspects are still poorly understood and therefore represent an exciting research frontier. Future studies that include larger adolescent samples and provide a more detailed description including symptom severity and comorbidity would contribute to a better understanding of this complex and painful condition.